Reasons behind family refusal to organ donation in Sabah, Malaysia - Chin, Su Na; P.K. Cheah; L.Y. Low; W.J. Ng (Faculty of Science and Natural Resources, 2020)
Despite increased public awareness and the increase in the number of pledged organ donors, the actual number of organ donation in Sabah remains low due to the high rejection rate to donation by family members. This retrospective study aims to discover the main reasons of family refusal to organ donation in Sabah, besides attempting to determine whether the reasons of family refusal were significantly associated to the background of the next-of-kin. Descriptive statistics were used to describe the demography of the deceased and the next-of kin, as well as the reason of refusal. Meanwhile, Chisquare test and Kruskal-Wallis test were implemented to identify the significant associations. Not knowing the wish of deceased, unwilling to let the deceased to suffer, and concern over funeral delay stand out to be the most predominant reasons of family refusal. However, none of the background factors are significantly associated with reasons of family refusal to organ donation.